Association of the relationship between eating behavior, parental feeding style and body weight in children - Ozcelik-Ersu, Dilek; Persil-Ozkan, Ozlem (Progress in Nutrition, 2021)
Objectives: The aim of this study was to investigate the effects of parental feeding styles and children’s eating behavior patterns on both low body weight and obesity. Methods: This study was a descriptive and cross-sectional. The cohort consisted of the preschool and elementary school parents (350 children) of a school in Istanbul/Turkey, 244 parents were participated between 15 April-15 June 2018. Children’s Eating Behavior Questionnaire and Parental Feeding Style Questionnaire were applied. Descriptive statistical methods were used to explain children’s characteristics. Parametric methods were used for variables with normal distribution and non-parametric statistical methods were used for data with abnormal distribution. Spearman’s rho was used to determine the relationship between scores obtained from both questionnaires and BMI. Mann-Whitney U test was used for non-normally distributed variables and t-test or independent variables was used to determine the difference between the mean scores according to gender. Results: The median age of the children was 7.3 (5-10) years. Mean BMI Z-score value was 0.4 ± 1.4. According to BMI Z- score; 4.9% (n: 12) were underweight, 56.6% (n: 138) were normal weight, 26.6% (n: 65) were overweight and 11.9% (n:29) were obese. Underweight children were picky about food consumption. Overweight/obese children were prone to both emotional overeating and under eating and enjoyed eating more. Parental emotional feeding style was associated with emotional overeating, under eating and food selectivity scores and they enjoyed eating more. Conclusion: Applying practical and reliable methods to assess nutritional habits may help to diagnose and prevent malnutrition problems early in childhood. Healthy nutrition behavior could be improved with proper parental feeding styles.